2022
DOI: 10.34133/2022/9783197
|View full text |Cite
|
Sign up to set email alerts
|

Design of Protein Segments and Peptides for Binding to Protein Targets

Abstract: Recent years have witnessed a rise in methods for accurate prediction of structure and design of novel functional proteins. Design of functional protein fragments and peptides occupy a small, albeit unique, space within the general field of protein design. While the smaller size of these peptides allows for more exhaustive computational methods, flexibility in their structure and sparsity of data compared to proteins, as well as presence of noncanonical building blocks, add additional challenges to their desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 190 publications
0
13
0
Order By: Relevance
“…While the hinge motion is thus important, several studies provide substantial evidence supporting the feasibility of designing and synthesizing peptide sequences that leverage functional amino acid sequences derived from proteins. 64–66 For example, Fowler et al (2021) 67 demonstrated selective P i adsorption and controlled desorption using a protein-derived P i -binding peptide sequence approximately 37× smaller than the PBP tested in our study. Immobilization of such peptide sequences and testing their P i binding potential in a range of conditions relative to water/wastewater is important moving forward to further evaluate the adsorbent's abilities relative to other adsorbents.…”
Section: Resultsmentioning
confidence: 49%
“…While the hinge motion is thus important, several studies provide substantial evidence supporting the feasibility of designing and synthesizing peptide sequences that leverage functional amino acid sequences derived from proteins. 64–66 For example, Fowler et al (2021) 67 demonstrated selective P i adsorption and controlled desorption using a protein-derived P i -binding peptide sequence approximately 37× smaller than the PBP tested in our study. Immobilization of such peptide sequences and testing their P i binding potential in a range of conditions relative to water/wastewater is important moving forward to further evaluate the adsorbent's abilities relative to other adsorbents.…”
Section: Resultsmentioning
confidence: 49%
“…98 Depending on the application, sequences that have already been discovered to have high affinity for a target can be utilized, iterated, or newly designed. 99 There is an opportunity in the active Janus particle community to utilize polypeptide specificity for biological targets, as well as utilize polypeptide affinity for solid materials including gold 100 and platinum. 101 For example, peptide-functionalized gold nanoparticles already serve as effective cell-targeting agents.…”
Section: Affinity Sequencesmentioning
confidence: 99%
“…Sequences that can selectively bind to targets have been utilized for drug delivery, nanomaterial assembly, biosensing, and protein purification . Depending on the application, sequences that have already been discovered to have high affinity for a target can be utilized, iterated, or newly designed . There is an opportunity in the active Janus particle community to utilize polypeptide specificity for biological targets, as well as utilize polypeptide affinity for solid materials including gold and platinum .…”
Section: Designing Peptides and Polypeptidesmentioning
confidence: 99%
“…One of the successful strategies to design affinity peptides involves starting from a fragment or motif predicted to possess binding affinity and improving upon it. 29 Following phage display screening, the screened peptide sequences were analyzed to identify common patterns or motifs by examining specific amino acid residues. In this study, we aimed to enhance selectivity and sensitivity along with the application of hydrogel-based fluorescence sensors by designing and synthesizing new peptides based on motifs observed in C7Cmer 2R-17/12mer 3R-12 (motif 1, NXXNXLXW(F)) and 12mer 3R-21/12mer 4R-30 (motif 2, F(W)XY(S)XH-(K)SXXGAW).…”
Section: Identification Of H3n2 Ha1 Specific Affinitymentioning
confidence: 99%
“…Designing of H3N2 HA1 Targeted Peptide. One of the successful strategies to design affinity peptides involves starting from a fragment or motif predicted to possess binding affinity and improving upon it 29. Following phage display screening, the screened peptide sequences were analyzed to identify common patterns or motifs by examining specific amino acid residues.…”
mentioning
confidence: 99%